THE REPRESENTATIONS OF INDONESIA IN THE SPEECH OF PRESIDENT SUSILO BAMBANG YUDHOYONO AND BARRACK OBAMA - Asrisa Asianto Putri, - (2011)
This research paper presents a Transitivity analysis from Functional Grammar of the representations of Indonesia in the speech of President Yudhoyono and Obama. "Representation is an activity in which language is used to say something meaningful about the world to other people" (Hall 1997:15). This research paper applied analysis of ideational meaning which is realized by transitivity analysis to identify the two speeches. The transitivity analysis was chosen because this kind of meaning deals with clauses as representation which is appropriate for this research paper. The analysis obtained textual evidence from the speech of President Yudhoyono and Obama through classifying every clause based on the type of process. Quantitatively it was found that in the speech of SBY, first position of process which occurred at most belongs to material process (32.91%). Second position belongs to mental process (26.65%) and third position which appeared at most is relational process (25.71%). Whereas in the speech of Obama, the process which occurred at most in first position is material process (39.08%), second is relational process (26.47%) and third is mental process (18.28%). However, those two speeches had same emphasis in order to represent Indonesia. Both presidents represented Indonesia in positive representations: as a country which 'is making impressive gains in the fight against corruption', 'plays a key role in the Asia Pacific', 'the largest country and the largest economy in Southeast Asia' and many others. Those representations are realized mostly through material and relational process. There is no evidence that show a negative portrayal of Indonesia. Each country has their own strength, whether President Yudhoyono or Obama did not point out that Indonesia is inferior than America or vice versa. President Yudhoyono and President Obama represent Indonesia as "the partner" not as "the competitor" of America.